THE INFLUENCE OF COMPENSATION, TEAMWORK, AND WORK MOTIVATION TOWARD JOB PERFORMANCE AT PT. TELU SUKSES BERSAMA IN CIKARANG - Muhammad Riqi; Erny Hutabarat (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2020)
ABSTRACTThe purpose of this study was to determine the factors that affect the performance ofemployee at PT Telu Sukses Bersama in Cikarang. The company has several ups and downs onperformance during year 2015-2019 and hit the lowest result in 2019. This study predicts thatthere were several factors that influence employee performance, namely compensation, teamwork,and work motivation based on the interview with HR staff. Total number of population was 306 (on25 June 2020) employees. Quantitative descriptive method was used where data was collectedthrough questionnaires with random sampling methods. Then data was analyzed using SPSS,Smart PLS, and Microsoft Excel 2010. The results showed that Compensation has significantinfluence on Job Performance, Teamwork has significant influence on Job Performance, also withWork Motivation has significant influence on Job Performance.Keywords: Compensation, job performance, teamwork, work motivation